Tổ chức dạy học chủ đề “Hiệu ứng nhà kính” (Khoa học tự nhiên 8) theo tiến trình nghiên cứu khoa học - Trần, Thị Ngọc Ánh; Lê, Thanh Trúc Thy (Tạp chí Giáo dục, 2025)
Offering insights into the transfer of heat energy, the theme “Greenhouse Effect” in Natural Science 8 renders a highly abstract and significant topic that poses many difficulties for learners and teachers in their teaching-learning processes. According to the scientific research process applied to this topic, the teaching method is highly effective in developing scientific thinking, natural science capacity, and practical skills for students. The teaching process includes the following steps: asking research questions, collecting information, proposing hypotheses, making test plans, implementing plans, synthesizing knowledge, and applying. The use of the scientific research process to teach this content among students is an activity through which they can better appreciate this subject via formulating questions, somewhat testing hypotheses, and planning experiments and research. Tests from pedagogical experiments showed that the method is practical and very effective. Students learn in an active atmosphere and acquire scientific thinking skills. According to the scientific research process, the teaching method improves learning efficiency, meets educational innovation expectations, and develops students’ natural science capacity. Research orientations will then be concerned with expanding the use of this method to other topics in the field of Natural Sciences.